2017
DOI: 10.1002/polb.24299
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of PEDOT films prepared by electrochemical polymerization

Abstract: Thermoelectric (TE) properties of flexible and freestanding poly(3,4-ethylenedioxythiophene) (PEDOT) films synthesized via galvanostatic polymerization of 3,4-ethylenedioxythiophene in propylene carbonate containing sulfated poly(bhydroxyethers) (S-PHE) as polymer electrolyte were elaborately studied. Both electrical conductivities (r) and Seebeck coefficients (S) of the PEDOT:S-PHE films were increased by decreasing the temperature (T) or by increasing the current density (J) during electrosynthesis. Possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In particular, the performance of the PEDOT lm produced using water/ methanol at the electropolymerization time of 10 s was superior to that of PEDOT lms produced using well-established, conventional electropolymerization methods. 51,52 The power factor of both PEDOT lms signicantly decreased as the electropolymerization time increased. The inset in Fig.…”
Section: Thermoelectric Properties Of Pedot Lmsmentioning
confidence: 99%
“…In particular, the performance of the PEDOT lm produced using water/ methanol at the electropolymerization time of 10 s was superior to that of PEDOT lms produced using well-established, conventional electropolymerization methods. 51,52 The power factor of both PEDOT lms signicantly decreased as the electropolymerization time increased. The inset in Fig.…”
Section: Thermoelectric Properties Of Pedot Lmsmentioning
confidence: 99%
“…Recently, Zhang et al tuned the TE performance of PEDOT films through electrochemical control of the oxidation states. Still, the power factor of the films was merely up to 7.9 μW m −1 K −2 …”
Section: Introductionmentioning
confidence: 96%
“…14 Still, the power factor of the films was merely up to 7.9 lW m 21 K 22 . 15 In contrast, the VPP method is simple and can overcome the aforementioned issues. Therefore, it is the best method to easily manufacture highly conductive PEDOT films.…”
Section: Introduction Poly(34-ethylenedioxythiophene) (Pedot)mentioning
confidence: 99%
“…P3HT, and PBTTT showed that PDPP3T has a higher power factor (25 μW.m -1 .K -2 ) than PBTTT (14 μW.m -1 .K -2 ), and comparable to that of P3HT (30 μW.m -1 .K -2 ) [131]. It is worth mentioning that PDPP3T films had a lower σ and higher S than other films even at low doping levels [95,131]. The optimized power factor obtained for PDPP3T films is 276 μW.m -1 .K -2 .…”
Section: Donor-acceptor P-type Polymermentioning
confidence: 88%